Biodiversity, the Human Microbiome and Mental Health: Moving toward a New Clinical Ecology for the 21st Century?. (3rd August 2016) - Prescott, Susan L.; Millstein, Rachel A.; Katzman, Martin A.; Logan, Alan C.
Abstract : Advances in research concerning the brain-related influences of the microbiome have been paradigm shifting, although at an early stage, clinical research involving beneficial microbes lends credence to the notion that the microbiome may be an important target in supporting mental health (defined here along the continuum between quality of life and the criteria for specific disorders). Through metagenomics, proteomics, metabolomics, and systems biology, a new emphasis to personalized medicine is on the horizon. Humans can now be viewed as multispecies organisms operating within an ecological theatre; it is important that clinicians increasingly see their patients in this context. Historically marginalized ecological aspects of health are destined to become an important consideration in the new frontiers of practicing medicine with the microbiome in mind. Emerging evidence indicates that macrobiodiversity in the external environment can influence mental well-being. Local biodiversity may also drive differences in human-associated microbiota; microbial diversity as a product of external biodiversity may have far-reaching effects on immune function and mood. With a focus on the microbiome as it pertains to mental health, we define environmental "grey space" and emphasize a new frontier involving bio-eco-psychological medicine. Within this concept the ecological terrain can link dysbiotic lifestyles and biodiversity on the grand scale to the local human-associated microbial ecosystems that might otherwise seem far removed from one another.